2009
DOI: 10.1007/s10508-009-9480-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sexual Coercion in Heterosexual and Non-Heterosexual Men and Women

Abstract: Heterosexual sex differences in evolved sexual interests, sexual scripts, and aggressive tendencies have each been hypothesized to be responsible for heterosexual sex differences in sexually coercive behavior. The current study compared the sexually coercive behavior of heterosexual and non-heterosexual men and women as a means of evaluating the explanatory capabilities of each of these hypotheses. A total of 414 participants were asked to provide information regarding their sexual coercion perpetration behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…The fact that men in our sample reported more experience as a victim of verbal sexual coercion conflicted with some prior findings (e.g., Struckman-Johnson et al, 2003;VanderLaan & Vasey, 2009), but not all. Some research has found that young men report similar levels of non-violent sexual coercion as women (22 vs. 24.5 % in a multinational study of college students by Hines, 2007, and 6.6 vs. 7.7 % in a national study of adolescents by Kaestle, 2009) or even higher levels of victimization than their female counterparts (21.9 vs. 10.4 % in a study of high-school students by Enosh, 2007).…”
Section: Men's Greater Victimizationcontrasting
confidence: 55%
See 2 more Smart Citations
“…The fact that men in our sample reported more experience as a victim of verbal sexual coercion conflicted with some prior findings (e.g., Struckman-Johnson et al, 2003;VanderLaan & Vasey, 2009), but not all. Some research has found that young men report similar levels of non-violent sexual coercion as women (22 vs. 24.5 % in a multinational study of college students by Hines, 2007, and 6.6 vs. 7.7 % in a national study of adolescents by Kaestle, 2009) or even higher levels of victimization than their female counterparts (21.9 vs. 10.4 % in a study of high-school students by Enosh, 2007).…”
Section: Men's Greater Victimizationcontrasting
confidence: 55%
“…Men with conservative gender role attitudes are also more likely to have personally obtained intercourse by using various coercive tactics, including lying, arguing, getting their female partner intoxicated, and through forceful rape (Muehlenhard & Falcon, 1990). Still others have found that the perpetration of sexual coercion varies with psychological masculinity for heterosexual and homosexual men and women (McConaghy & Zamir, 1995;VanderLaan & Vasey, 2009). VanderLaan and Vasey, for example, found that heterosexual men's greater use of verbal sexual coercion compared to non-heterosexual men was explained by differences in masculinity between these two groups, and suggested that future research examine whether performing nonphysical coercion can be attributed to adherence to scripts for masculine sexuality.…”
Section: Heteronormativity and Sexual Coercionmentioning
confidence: 99%
See 1 more Smart Citation
“…243-244) With culture erased (here, in its place, we find the euphemism "imitation"), gay and lesbian brains can be the reasons why "pre-gay" boys and girls are respectively less and more aggressive than "normal" boys and girls (Blanchard, McConkey, Roper, & Steiner, 1983); why straight men and lesbian women are more adept than gay men and straight women at throwing a ball at a target from a few feet away (J. Hall & Kimura, 1995); why gay men's verbal fluency is superior to the other three groups' (Rahman, Abrahams, & Wilson, 2003); why they are less likely than straight men to have committed acts of sexual coercion (VanderLaan & Vasey, 2009); why they are "over-represented" in professional dance (Bailey & Oberschneider, 1997); and so on. The "stereotype about 'feminine' gay men and 'masculine' lesbians … contains a substantial kernel of truth" (LeVay, 2011, p. 125), because the average homosexual brain is a patchwork of gender-inverted traits, some of which appear detectable by gaydar.…”
Section: A Queer Interpretationmentioning
confidence: 99%
“…Scripting theory has been extensively used to explore many aspects of sexual behaviour, including sexual initiation patterns (Dworkin and O’Sullivan 2005), portrayals of sexuality in the adolescent media (Carpenter 1998, Kim, et al 2007), changes in sexual practices over time (Gagnon and Simon 1987), patterns of sexual initiation and decision‐making among women (Dworkin et al 2007) and later‐life sexual experiences (Hurd 2006). The approach has proved useful in explaining, for instance, the disjuncture between current and desired patterns of sexual practices; (Dworkin and O’Sullivan 2005) gendered differences in both consensual and non‐consensual heterosexual interactions (Krahé et al 2007a, 2007b, Turchik et al 2009, Vanderlaan and Vasey 2009) and discordance in gender perceptions of partners’ preferences with regard to the duration of sexual activity (Miller and Byers 2004). Thus far, despite its potential for enhancing understanding of sexual experience, sexual scripting theory has rarely been applied to sexual function.…”
Section: Introductionmentioning
confidence: 99%